Community Empowerment in Postpartum Mothers' Behavior Towards Breast Milk Dams in Ladang Bambu Village, Medan Tuntungan District - Widia Astuti Tanjung; Cahya Cahya (Benih : Journal of Midwifery, 2024)
The postpartum period begins after the placenta is born and ends when the reproductive organs return to their pre-pregnancy state. This period is a critical period for both the mother and the baby, so it needs to be considered. One of the problems during the postpartum period is breast milk engorgement. Breast milk engorgement can interfere with the comfort of postpartum mothers and hinder the effectiveness of exclusive breastfeeding. An important role in the success of providing exclusive breastfeeding is efforts to prevent breast milk engorgement in postpartum mothers, namely by empowering postpartum mothers to pay attention to good and correct breastfeeding techniques. By providing knowledge to postpartum mothers about the proper handling of breast milk engorgement, it is hoped that mothers can change their behavior to prioritize proper exclusive breastfeeding. Based on the results of a survey conducted on July 23, 2024 in Ladang Bambu Village, Medan Tuntungan District. The method in this community service uses interactive communication, education and direct training to 22 postpartum mother participants in Ladang Bambu Village, Medan Tuntungan District. The results of this community service activity were an increase in knowledge from postpartum mothers who had babies with an average of 33.2 increasing to 68.7. The conclusion is that there is an increase in mothers' knowledge and skills regarding the management of breast milk dams after education regarding breast milk was carried out in Ladang Bambu Village, Medan Tuntungan District.